Object of violation of financial control requirements - R. D. Troychuk (Law and Safety)
The article is devoted to the study of the essence of the concept and types of objects of administrative offenses related to the violations of financial control. Scientific approaches to determining the constituent elements of the object of this administrative offense were presented. It was found that for the proper qualification of an administrative offense related to violation of financial control, and hence the definition of the scope of administrative liability as a measure of administrative coercion, it is important to take into account the specifics of public relations (as an object of encroachment) and the scope in which they arise. It was clarified the role of the object of administrative offense related to the violation of the financial control requirements in the qualification and systematization of the domestic administrative tort law. The scientific views on the definition of the object of the specified administrative offense was analyzed, the author offered his own definition of the general, generic, specific and direct objects. The general object of violation of the requirements of financial control should be understood as the whole set of public relations in the field of preventing and combating corruption, which is protected by administrative and tort regulations. The generic object of the violation of the requirements of financial control is public relations, which provide the established procedure for preventing and combating corruption. Given that the provisions of Article 172 of the Code of Administrative Offenses of Ukraine contain various forms of acts for which liability is provided, the composition of violations of financial control contains a specific object, which is proposed to admit a group of homogeneous social relations, allocated within the framework of a generic object related to the procedure for submitting a declaration of a person authorized to perform the functions of the state or local government, opening a foreign currency account in a non-resident bank institution and notification of significant changes in property status, as well as submitting knowingly false information in the declaration of a person authorized to to perform the functions of the state or local self-government. The direct object of violation of the requirements of financial control is requirements, prohibitions and restrictions which protected by administrative-tort sanction established by the Law of Ukraine “On Prevention of Corruption” and other regulations, and arising in connection with the declaration of a person authorized to perform state functions or local government.